Improving Digitalization Projects with the Help of Agile Project Management in Finnish Manufacturing Companies - Ayer, Amit (My University, 2026)
This thesis examines the role of agile project management on the success of digitalisation projects in Finnish manufacturing companies and when hybrid governance is the most effective. The research is driven by the strategic significance of industrial digitalisation and the struggles to deliver operational and business value from digital investments. Although agile project management has been well studied in software and knowledge-intensive industries, there has been a lack of research on the use of agile approaches in manufacturing projects that are affected by socio-technical complexity, technological legacy, cybersecurity concerns, and the need for business continuity. The thesis follows a pragmatist, qualitative dominant secondary data-based research design. It incorporates a systematic review of the literature on agile project management, hybrid governance, manufacturing digitalisation, benefits realisation, and dynamic capabilities, and policy and statistical data from Finnish and European institutional sources. The analysis is informed by a conceptual model whereby agile and hybrid governance impact project performance via mechanisms such as a faster rate of learning, coordination across functional areas, risk detection and avoidance, and minimisation of rework. The results show that agile practices in digitalisation projects such as iterative development, customer feedback, dynamic planning, and multi-functional integration, can improve project performance, especially in the components that involve uncertainty and exploratory learning. But their impact is substantially conditioned by manufacturing-specific constraints, such as the complexity of IT/OT integration, cybersecurity and regulatory constraints, procurement rigidity and need for system uptime. These boundaries restrict the use of agile practices in manufacturing operations. As such, hybrid governance emerges as the most suitable and fit-for-context governance mechanism for Finnish manufacturing digitalisation initiatives. Hybrid governance allows for the use of agile governance mechanisms for innovation-led parts and plan-based governance mechanisms needed for stability, compliance and security. The doctoral thesis helps to understand the interplay between governance mechanisms and structural constraints from the perspective of socio-technical systems theory, dynamic capabilities theory and contingency theory. It offers a governance view to manufacturing organisations strategically aiming to enhance digitalisation outcomes with context-specific project management approaches. KEYWORDS: agile project management; hybrid governance; digitalisation; digital transformation; Finnish manufacturing; sociotechnical systems; benefits realisation
Keywords: digitalisation; project management; project leadership; agile methods; projects; industry; manufacturing; industrial companies; software development; development projects; Strategic Project Management; Master’s Programme in Industrial Engineering and Management